2005
DOI: 10.1111/j.1365-2427.2005.01392.x
|View full text |Cite
|
Sign up to set email alerts
|

Soluble nitrogen and phosphorus excretion of exotic freshwater mussels (Dreissena spp.): potential impacts for nutrient remineralisation in western Lake Erie

Abstract: 1. Recent increases in phytoplankton biomass and the recurrence of cyanobacterial blooms in western Lake Erie, concomitant with a shift from a community dominated by zebra mussels (Dreissena polymorpha) to one dominated by quagga mussels (D. bugensis), led us to test for differences in ammonia-nitrogen and phosphate-phosphorus excretion rates of these two species of invasive molluscs. 2. We found significant differences in excretion rate both between size classes within a taxon and between taxa, with zebra mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
105
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 154 publications
(115 citation statements)
references
References 61 publications
8
105
0
2
Order By: Relevance
“…Most likely, differences in specific metabolic rates could be related to differences in SRP excretion rate of species. Interspecies differences in SRP excretion rates were found also in other studies: between the rotifera Euchlanis dilatata (18-19 ºC) and other rotifers (Gulati et al, 1989) as well as between Dreissena polymorpha and D. bugensis (Conroy et al, 2005). At the same time, Devine and Vanni (2002) showed that differences in SRP excretion rate between taxa are not significant and this rate depend mostly on temperature and biomass.…”
Section: Discussionsupporting
confidence: 61%
“…Most likely, differences in specific metabolic rates could be related to differences in SRP excretion rate of species. Interspecies differences in SRP excretion rates were found also in other studies: between the rotifera Euchlanis dilatata (18-19 ºC) and other rotifers (Gulati et al, 1989) as well as between Dreissena polymorpha and D. bugensis (Conroy et al, 2005). At the same time, Devine and Vanni (2002) showed that differences in SRP excretion rate between taxa are not significant and this rate depend mostly on temperature and biomass.…”
Section: Discussionsupporting
confidence: 61%
“…However, during the sampling period from August to September; an exotic invasive species in Ireland, Zebra mussels (Dreissena polymorpha) were evident at highest concentrations on the eastern side of the lake at Coole Bay. The filtering activities of zebra Characteristics of lake dissolved organic matter mussels have been shown to have a large ecosystem-level influence on nitrogen cycling [49][50][51] and organic nitrogen concentrations decrease in water columns in microcosms with live zebra mussels. [52] It is therefore possible that the filtering activities of Zebra mussels result in recycling of larger organic nitrogen compounds such as phenylalanine.…”
Section: Dom Variabilitymentioning
confidence: 99%
“…An additional threat posed by cyanobacteria was found to come from Anabaena and Microcystis, which are toxigenic cyanobacteria (Watson et al, 2016). Cyanobacteria growth is promoted by changes of internal and external nutrient loadings and increased temperature (Conroy et al, 2005;McCormick and Fahnenstiel, 1999). In addition, studies have reported that climate change is predicted to expedite to temperatures and stratification patterns beneficial for cyanobacterial growth (Paerl and Huisman, 2008;Wagner and Adrian, 2009) and contribute to hypoxia (Lynch et al, 2010).…”
Section: Discussionmentioning
confidence: 99%